Evaluation of Road Geometry at the Toll Gate to Kertajati International Airport: Case Study of Kertajati Toll Gate Road - Angga Pratama; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2024)
Many cities have adapted to overcome the challenges they face. Resources and weather changes are the main factors that make cities around the world intend to advance urban infrastructure in their countries. Majalengka is experiencing rapid economic growth marked by several major developments such as BIJB Airport, Kertajati toll gate, bridges, and many more. Especially the road to the Kertajati area, which has the West Java International Airport. Quick and precise planning is one of the first steps to achieve this. These findings also revealed that the excavation and embankment volumes required by the road planning requirements were 156203.72 m3 for the excavation and 36412.31 m3 for the embankment.